"But I Thought I Knew That!" Student Confidence Judgments on Course Examinations in Introductory Psychology. (October 2015) - Nevid, Jeffrey S.; Cheney, Brianna; Thompson, Clarissa
Students in an introductory psychology class rated their level of confidence in their answers to exam questions on four multiple-choice exams through the course of a semester. Correlations between confidence judgments and accuracy (correct vs. incorrect) at the individual item level showed modest but significant relationships for item sets scaled to levels in Bloom's taxonomy of educational objectives. We also found stronger relationships between confidence judgments and accuracy for items scaled to lower levels in Bloom's taxonomy. Overconfident judgments occurred significantly more often among the lowest performing students. These results underscore the need for students to become more accurate appraisers of their knowledge, which may help them correct gaps in their knowledge by taking steps to prepare more effectively for examinations.